NEK9-dependent proliferation of cancer cells lacking functional p53 - Kurioka, Daisuke (Nature Publishing Group, 2014)
Dysfunction of the p53 network is a major cause of cancer development, and selective elimination of p53-inactivated cancer cells therefore represents an ideal therapeutic strategy. In this study, we performed a microRNA target screen that identified NEK9 (NIMA-related kinase 9) as a crucial regulator of cell-cycle progression in p53-inactivated cancer cells. NEK9 depletion selectively inhibited proliferation in p53-deficient cancer cells both in vitro and in vivo. The resultant cell-cycle arrest occurred predominantly in G1 phase, and exhibited senescence-like features. Furthermore, NEK9 repression affected expression of a broad range of genes encoding cell-cycle regulators and factors involved in mRNA processing, suggesting a novel role for NEK9 in p53-deficient cells. Lung adenocarcinoma patients with positive staining for NEK9 and mutant p53 proteins exhibited significantly poorer prognoses, suggesting that expression of both proteins promotes tumor growth. Our findings demonstrate that a novel NEK9 network regulates the growth of cancer cells lacking functional p53.